PENYULUHAN PENGUATAN PROFIL PELAJAR PANCASILA GUNA MENANGKAL KENAKALAN REMAJA PADA SISWA SMA TERPADU PELITA BANGSA LONTAR KECAMATAN TIRTAYASA KABUPATEN SERANG PROVINSI BANTEN: - - Sanin Sudrajat; Saepudin Saepudin; Rr. Nadhira Harsari; Munawaroh Munawaroh; Mohamad Bayi Tabrani; Muhammad Saleh; Meiby Zulfikar; Ahmad Suganda; Luis Fiska Rahayu; Imamudin Imamudin (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This service activity discusses strengthening the profile of Pancasila to ward off juvenile delinquency, especially high school students. This service aims to strengthen the character and competence of high school students in implementing the Pancasila Student Profile program in the school environment. The Pancasila Student Profile means that Indonesian students are lifelong learners who have Pancasila competence and character which is manifested in 6 (six) Pancasila student profiles, namely faith and piety, global diversity, mutual cooperation, independence, critical and creative thinking. This service methodology goes through a preliminary survey stage to find out the situation at the service location regarding the implementation of the Pancasila Student outreach program, then observation or implementation of activities involving 20 people consisting of school principals, teachers, students and education staff. This service activity was carried out at Pelita Bangsa Lontar Integrated High School, Tirtayasa District, Serang Regency. The counseling on strengthening the profile of Pancasila students went smoothly according to plan.  This activity received a positive response from the participants and they were very enthusiastic. The material presented is in the form of Pancasila student profiles which are then combined with religious values and local wisdom which has opened the horizons of thinking of the counseling participants. With good implementation and understanding of the Pancasila student profile, the PkM team hopes that students as the nation's next generation can grow and develop into individuals who are faithful, devout, have noble character and diversity. Students are expected to have an independent attitude, the ability to work together and work together, critical thinking skills, and high creativity to bring positive effects to society, the nation and the state and can ward off negative acts such as juvenile delinquency that occur among students